INNV-28. A PILOT STUDY EVALUATING THE FEASIBILITY OF USING AN ULTRA-FAST DIGITAL CONFOCAL MICROSCOPY SCANNER FOR REAL-TIME INTRA-OPERATIVE BRAIN TUMOUR DIAGNOSIS. (14th November 2022) - Bolton, William; Ramakrishnan, Piravin; Reveendran, Dharsshini; Chakrabarty, Arundhati; Mathew, Ryan
Abstract: INTRODUCTION: Real-time intra-operative brain tumour tissue analysis in the operating room (OR) can shorten turnaround times and facilitate repeated sampling; the latter can improve diagnostic accuracy and guide resection to maximise extent. We evaluated the feasibility of using an ultra-fast confocal microscopy scanner (Histolog®, SamanTree Medical SA) in the OR for real-time intra-operative brain tumour tissue diagnosis. This study is the first use of Histolog® on primary human brain tissue globally. METHODS: An observational pilot study with varying brain tumour types was conducted in a tertiary UK brain tumour centre. Multiple, freshly excised tissue samples were stained with Acridine Orange, and images captured within 60 seconds on Histolog® in the OR in parallel to current diagnostic pathways. A Consultant Neuropathologist performed a blinded correspondence assessment between Histolog® and current gold standard histopathology. Qualitative logging of diagnostic features was performed. RESULTS: Cases studied (n=12) included glioma, metastasis, meningioma, schwannoma, and pituitary adenoma. Concordance between Histolog® and traditional (frozen section) intra-operative histopathological diagnosis was 83% (10/12 cases). One Histolog® case demonstrated superior diagnostic accuracy to frozen section. Histolog® images demonstrated specific diagnostic features such as clusters of cohesive epithelioid cells (metastatic carcinoma), sheet-like variably cellular and pleomorphic cells (gliomas), diffuse sheet-like monomorphic round nuclei (pituitary adenoma), elongated spindle cells (schwannoma), and nodular architecture and oval nuclei (meningioma). DISCUSSION: Ultra-fast confocal microscopy scanning with Histolog® is feasible in the OR and Histolog® image resolution is adequate to identify histopathological features necessary for intra-operative brain tumour diagnosis. Training and clinico-radiological details are important in minimising discordance. A larger study with greater numbers and tumour types will now be performed to define an optimal scanning protocol and determine the strengths and limitations of the technology. Future studies should investigate the effect of real-time margin zone analysis on extending resection.